Biofilms of Klebsiella pneumoniae are tolerant to disinfection by peracetic acid under conditions relevant for endoscope reprocessing - Arvand, Mardjan; Konrat, K.; Csertö, D.; Richter, A. M. (The journal of hospital infection, 2026)
Background - Klebsiella pneumoniae is a prominent cause of healthcare-associated infections. Carbapenem-resistant K. pneumoniae (CRKP) is considered a serious public health threat and has been increasingly linked to endoscopy-associated outbreaks. Biofilm formation in endoscope channels contributes to increased antimicrobial tolerance, potentially compromising disinfectant efficacy during reprocessing. This study evaluated the efficacy of peracetic acid (PAA), a commonly used disinfectant in endoscope reprocessing, on K. pneumoniae in planktonic and biofilm form. - Methods - Disinfectant efficacy was assessed using the suspension test EN 13727 and the Bead Assay for Biofilms. Five K. pneumoniae strains were tested: two CRKP associated with endoscopy outbreaks, two carbapenem-susceptible clinical strains and ATCC 13883. - Findings - All strains were susceptible to PAA in suspension test, with 0.001-0.01% PAA achieving 5 log10 cfu reduction within 10 min. In contrast, biofilm-residing cells required higher concentrations (0.075-0.2% PAA, 10 min) for equivalent efficacy. Clinical strains were notably more tolerant than ATCC 13883. Under standard endoscope reprocessing conditions (PAA 0.075%, 5 min, 37 °C), biofilms of all strains exhibited tolerance, failing to meet the 5 log10 cfu reduction threshold. In contrast, intensified endoscope reprocessing conditions (0.15% PAA, 10 min, 37 °C) resulted in successful biofilm disinfection. - Conclusions - Biofilms of K. pneumoniae, including CRKP, exhibit marked tolerance to standard concentrations of PAA used in endoscope reprocessing. These data suggest that routinely used disinfection conditions may not be sufficient when biofilm formation is likely. Disinfection parameters in areas at high risk of biofilm contamination, e.g., endoscope reprocessing, and in the context of CRKP outbreaks should be reviewed and adjusted if necessary.
Online verfügbar: 4. November 2025, Artikelversion: 25. November 2025
Gesehen am 26.02.2026